If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = 8x + -7x + 4 Reorder the terms: 3 = 4 + 8x + -7x Combine like terms: 8x + -7x = 1x 3 = 4 + 1x Solving 3 = 4 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3 + -1x = 4 + 1x + -1x Combine like terms: 1x + -1x = 0 3 + -1x = 4 + 0 3 + -1x = 4 Add '-3' to each side of the equation. 3 + -3 + -1x = 4 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 4 + -3 -1x = 4 + -3 Combine like terms: 4 + -3 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1
| y^3(3-4x^2)=7x-y^4 | | 2(x+3/4)=9(1/6-x) | | -8x+9x+6=9 | | 6x-8x+2=-13 | | 35=x+(2x-1)+(3(2x-1)+3) | | 35=x+(2x-1)+(3(2x-1)+2) | | 35=x+(3x-1)+(4(3x-1)+2) | | x(x+5)+1=(x+6)(x+6) | | 7=r^(1/2) | | 6x-3-5x=-13-5 | | 2cotx/sinx | | 35=x+(3x-1)+(2(2x-1)+2) | | M/10=4 | | 8x-7x-6=7-13 | | 10(x+2/15)=8(x-7/3) | | 35=x+(2x-1)+(4(2x-1)+2) | | 9x-16=3x+20 | | X/2=50 | | 4x-5=3x-3 | | -5=7x+1-6x | | 35=x+(2x-1)+(14(2x-1)+2) | | 115+5x=240 | | 3.5x+5=50.50 | | -15=-6r-1-2 | | 25x+57=232 | | M^(3/4)=27 | | 15x-17+2x=-34 | | 5x+9-4x=-1 | | 5x-1=4x-4 | | 6+3a+4a=-8 | | 5x-1=4x-1 | | 3x+9-2x=5 |